1994
DOI: 10.1073/pnas.91.11.5124
|View full text |Cite
|
Sign up to set email alerts
|

The human Ha-ras oncogene induces genomic instability in murine fibroblasts within one cell cycle.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
0
3

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(132 citation statements)
references
References 28 publications
7
122
0
3
Order By: Relevance
“…Indeed, the same HA-RAS allele was previously reported to increase the intracellular level of reactive oxygen species in human fibroblasts, which could trigger various types of DNA damage . Of note, human oncogenic HA-RAS alleles were reported to induce genomic instability in certain cell types (see for example (Denko et al, 1994;Woo and Poon, 2004) but not in others , as in our case with human fibroblasts (Figure 2). The reason of these discrepancies are not known but could rely on cell-type differences, culture conditions and/or levels of Ras activation.…”
Section: Induction Of Different Types Of Trf2 Dysfunction In Telomerimentioning
confidence: 54%
“…Indeed, the same HA-RAS allele was previously reported to increase the intracellular level of reactive oxygen species in human fibroblasts, which could trigger various types of DNA damage . Of note, human oncogenic HA-RAS alleles were reported to induce genomic instability in certain cell types (see for example (Denko et al, 1994;Woo and Poon, 2004) but not in others , as in our case with human fibroblasts (Figure 2). The reason of these discrepancies are not known but could rely on cell-type differences, culture conditions and/or levels of Ras activation.…”
Section: Induction Of Different Types Of Trf2 Dysfunction In Telomerimentioning
confidence: 54%
“…Several lineage 3 and 5 mice are tumor free, unilateral tumors are common, and tumors appear with long latency. This implies that at least a second genetic event is necessary for the onset of thyroid C-cell tumorigenesis: either directly induced by ras, such as chromosomal breakage and genomic instability leading to mutations in tumor suppressor genes such as p53 or Rb (Denko et al, 1994), or an independent stochastic event occurring by chance with increasing age. The high incidence of MTC in thyroids from rascal transgenic mice but not in any normal littermates would favor a direct linkage between expression of activated ras and development of Ccell tumors.…”
Section: Discussionmentioning
confidence: 99%
“…As damage is present in the chromosomes of cells treated with both nocodazole and z-VAD-fmk, breakage appears to be caspase-independent. Other works have shown that DNA damage can be induced by overexpression of oncogenes such as Myc and Ras (Denko et al, 1994;Felsher and Bishop, 1999;Vafa et al, 2002;Pusapati et al, 2006), suggesting that forced cell cycle entry under inappropriate conditions triggers chromosome breaks. Hence, a variety of signals monitoring cell cycle progression, including mitotic surveillance, may converge to activate chromosome breaks and finally the removal of unwanted cells via the classical p53-dependent apoptotic process.…”
Section: Which Features Trigger Dna Breaks?mentioning
confidence: 99%